2022
DOI: 10.7759/cureus.22750
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Combination of a Strong Interferon Inducer Viral Vector With Low Doses of Nivolumab Plus Ipilimumab Could Provide Functional Cure in Chronic Hepatitis B Virus infections: Technical Report Proposing a New Modality

Abstract: Based on the recommendation of the International Coalition to Eliminate hepatitis B virus (ICE-HBV), we intend to mimic the spontaneous resolution of HBV infection to achieve a functional cure of chronic hepatitis B virus (HBV) infection. To this end, we propose sequential targeting of the innate and adaptive host immune responses. Long-term suppression of HBV replication and hepatitis B surface antigen (HbsAg) production will be achieved first by inducing a strong innate immune response. The clinically valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Viruses have the unique ability to affect hundreds of genes with minimal genomic burden [ 26 ]. The small dsRNA genome of IBDV, for example, activates many IFN-related genes (toll-like receptor 3 (Tlr3), toll-like receptor 9 (Tlr9), Z-DNA binding protein 1 (Zbp1), IFN-activated gene 204 (Ifi204), IFN-gamma (IFN-g)) [ 8 ]. In the absence of adaptive immunity, the IFN system can control most, if not all, virus infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Viruses have the unique ability to affect hundreds of genes with minimal genomic burden [ 26 ]. The small dsRNA genome of IBDV, for example, activates many IFN-related genes (toll-like receptor 3 (Tlr3), toll-like receptor 9 (Tlr9), Z-DNA binding protein 1 (Zbp1), IFN-activated gene 204 (Ifi204), IFN-gamma (IFN-g)) [ 8 ]. In the absence of adaptive immunity, the IFN system can control most, if not all, virus infections.…”
Section: Discussionmentioning
confidence: 99%
“…Most viruses produce dsRNA at some point during their replication cycle activating the IFN gene defense system. The IBDV genome is composed of dsRNA, which induces one of the strongest IFN responses among viruses [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In stark contrast to the systemic toxic interferon-α-2b (IFNα2b) therapy, which may require dose modification or discontinuation, only minimal flu-like side effects were observed during IBDV superinfection therapy, even in parenchymally decompensated severe hepatitis patients [ 20 , 21 , 22 , 23 ]. One of the reasons for this difference could be that IFN receptors are virtually ubiquitously expressed in all cell membranes, and, following the interaction of IBDV with host cells, its dsRNA is recognized by specific receptors, which activate several gene families from within the cells.…”
Section: The Rationale Of Using Repurposed Ibdv Veterinary Vaccine To...mentioning
confidence: 99%
“…Many studies have observed that HBV infection upregulated one or more checkpoints expression on T cells or NK cells 21–23 . While still in early stages, basic and clinical data suggest that blockade of CTLA‐4 and PD‐1 can be beneficial in treating chronic HBV infection in some patients, but failed in others with unknown mechanisms 24–26 . Therefore, understanding the mechanism of immune checkpoint blockade therapies helps broaden the treatment options for chronic HBV infection.…”
Section: Introductionmentioning
confidence: 99%